Intracorporeal urinary diversion robot-assisted radical cystectomy versus open radical cystectomy: a systematic review - Nainggolan, Hoshea Jefferson; Rahman, Fakhri; Putera, Eka Setiawan Ananta (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Radical cystectomy is the standard treatment for advanced bladder cancer, with open surgery associated with significant perioperative morbidity. This study aimed to compare efficacy, safety, and cost-effectiveness of robotic-assisted versus open radical cystectomy (ORC) with intracorporeal urinary diversion (ICUD). METHODS A systematic review was conducted across databases (PubMed, Cochrane Library, ClinicalTrials.gov, and Google Scholar) following Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines, with the following keywords: “robotic-assisted cystectomy”, “open cystectomy”, “intracorporeal urinary diversion”, “bladder cancer”, “perioperative results”, “complications”, and “oncological efficacy”. Only studies published in the last 10 years were included, with literature searching completed in December 2024. RESULTS 8 studies comparing robot-assisted radical cystectomy (RARC) with ICUD to ORC were included. RARC with ICUD showed reduced blood loss, fewer transfusions, shorter hospital stays, and faster recovery with earlier bowel function, but longer operative times. Recurrence and survival, were similar between both approaches. CONCLUSIONS RARC with ICUD is a promising alternative to open cystectomy, providing perioperative benefits and faster recovery while maintaining equivalent oncologic outcomes. However, higher initial costs and technical complexity must be considered. Further research should assess quality of life, functional recovery, and overall healthcare impact.